Do social media literacy skills help in combating fake news spread? Modelling the moderating role of social media literacy skills in the relationship between rational choice factors and fake news sharing behaviour. (January 2023) - Wei, Lihong; Gong, Jiankun; Xu, Jing; Eeza Zainal Abidin, Nor; Destiny Apuke, Oberiri
Highlights: Trust in social media had a greater effect on fake news sharing behaviour. Social media literacy skills act as an effective moderator of fake news. The rational choice affects social media users fake new sharing. Those with low social media literacy skills have more inclination to share fake news. Abstract: This study modelled the rational factors that predict fake news sharing behaviour. It also tested the moderating role of social media literacy skills. The focus was on social media users in Nigeria. An online survey was conducted to gather the responses from participants across Nigerian geopolitical zones. Structural equation modelling (SEM) Smart PLS 3.6 was used to analyse the data. We found that information sharing, the news finds me perception, trust in social media and status-seeking lead to fake news sharing among social media users in Nigeria. Specifically, trust in social media and status-seeking had a greater effect on fake news sharing behaviour. We also found that social media literacy skills significantly moderate the relationship between information sharing, status-seeking, the news finds me perception, trust in social media and fake news sharing in such a way that the effects/relationships are stronger among those with low social media literacy skills. This outcome contributes to theory and practice which was highlighted in the concluding aspect of this study.